Low Carbon Concrete Possibilities: EPD and Regulations in Northern Periphery and Arctic - Iveta Novakova; Priyadharshini Perumal; Andrzej Cwirzen; Olafur Haralds Wallevik (10th MATBUD’2023 Scientific-Technical Conference, 2023)
Concrete is one of the most common building materials in the Northern Periphery and Arctic, and therefore we should pay attention to its quality while reducing its carbon footprint. The concrete industry has established many measures to limit greenhouse gas emissions from concrete, as stated in the environmental product declaration (EPD). The most significant contributor is cement (common dose between 250 and 600 kg per 1 m3 of concrete) in a concrete binder. Aside from the use of alternative fuels for cement production, new alternative materials for cement replacement are being sought. Those materials are called supplementary cementitious materials and mainly originate from industrial waste streams. Some of the materials are already standard and limited by the maximum allowed replacement, and some are new and still under investigation. The benefits and limitations of low-carbon concrete regulations in Norway, Sweden, Iceland, and Finland are demonstrated on three different concrete mixes in this article. The sorting of a reference mix and two low-carbon concrete mixes according to 4 different systems showed the informative character of the Icelandic system and the underestimation of possibilities for the carbon footprint of concrete in the Swedish classification system.